An analytic problem in combinatorial structures - Eugenijus Manstavičius; Rimantas Skrabutėnas (Lietuvos Matematikos Rinkinys)
An asymptotical formula for the Taylor coefficients of the generating series appearing in combinatorics is obtained. It is applied to derive a formula for the number of multisets of increasing weight.